Funkcje wybranych typów derywatów w polszczyźnie familijnej XIX stulecia (na podstawie korespondencji małżeńskiej Zofii Kraszewskiej) - Olma, Marceli (Stylistyka, 2021)
The paper prepared on the basis of 842 hand-written letters of Zofia Kraszewska to her husband Józef Ignacy, is the author’s next publication of 19th century epistolography.Cosidering the specific features of family letters the author starts from the theory of literaturę, pragmatics and sociolinguistics, which describes variant of language in different social groups.Then he presents some types of derivatives used by Kraszewska to show to the addres- see the situation context of writing, to express her permanent sensitives and temporary affections, as well as to fortify the pragmatic impact of particular letters. They are the equivalent of conversation and should compensate the lack of face-to face contact bet- ween the wife and her lamous husband.